Exploring the coverage of three non-intimate partner femicide incidents in the Weekend Argus’ Saturday and Sunday editions online in 2019 – A case study - Gool, Kauthar (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.